Upaya Penguatan Kelembagaan Pasca Izin Perhutanan Sosial Kelompok Tani HKm Ulusena di Kabupaten Konawe Selatan - Diny, Sakinah Mulia; Wardaya, Wirya; Hendrati, Ignatia Martha (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2025)
This community service is driven by the lack of knowledge among the community regarding institutional matters after the issuance of the social forestry permit for the HKm Ulusena farmer group. This activity aims to reinforce the institution of the farmer group in HKm Ulusena, located in South Konawe. The method used in this service activity is CBPR (Community-Based Participatory Research), which focuses on mentoring that emphasizes collaboration between mentors and the group. This mentoring activity lasted for three months and focused on institutional development, with a total of 132 members of the Forest Farmers Group participating.There were several stages of mentoring, including problem and potential identification, participatory planning, training and empowerment, institutional strengthening, and assessment and contemplation. The effects of the mentoring include an increase in the community's knowledge of the importance of institutions in social forestry, improvement in skills, and the completion of institutional documents such as RKPS, RKT, and AD/ART. Therefore, the HKm Ulusena farmer group is expected to continue to grow, improving its ranking within the KUPS system